Daily lives of university students in the health area during the beginning of the Covid-19 pandemic in Brazil - Mata, Luciana Regina Ferreira da; Pessalacia, Juliana Dias Reis; Kuznier, Tatiane Prette; Neto, Priscila Kelly da Silva; Moura, Caroline de Castro; Santos, Fernando Ribeiro dos (Investigación y Educación en Enfermería, 2021)
Objective. To determine the main changes that took place in the daily lives of students in the health area during the beginning of the Covid-19 pandemic in Brazil. Method. This is a cross-sectional study, carried out from May to June 2020, with 1786 students over 18 years old, regularly enrolled in health courses at higher education institutions in five regions of Brazil. Sampling was by convenience, typified as snowball. In order to collect data, an instrument to describe the sociodemographic profile and the daily lives of students during the pandemic period was used, which was applied via a digital platform on the web. Results. The main changes that took place in the daily lives of academic students in the health area in the face of the Covid-19 pandemic in Brazil are related to lower productivity; difficulty concentrating; increased hours of sleep, use of electro-electronic equipment and weight; poorer quality of food; higher consumption of food, legal and illegal substances and medications (mainly analgesics, anxiolytics and antidepressants); less interest in personal appearance; and greater contact with relatives. Regarding emotional changes, it should be underlined the complaints of anxiety, stress, anguish, confusion, helplessness and depression. Conclusion. During the beginning of the Covid-19 pandemic in Brazil, the students in the health area experienced several changes in their daily lives, which deserve special attention from higher education institutions and health systems, envisioning interventions to minimize health risks to this population.